2008
DOI: 10.1177/0022022107311843
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Attributions and Ethnocentrism in the Indian Subcontinent

Abstract: Predictions of Pettigrew's ultimate attribution error were investigated among 148 Indians (91 Hindus and 57 Muslims) and 145 Pakistanis (107 Muslims and 38 Hindus) in the Indian subcontinent. Using hypothetical scenarios, the first prediction, that negative behavior would be attributed more to dispositional than situational factors for out-group compared to in-group actors, received little support. The second prediction, that positive out-group behavior would be attributed more to situational circumstances, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 33 publications
4
12
1
Order By: Relevance
“…The out-group derogating attribution tendency, which is also part of the intergroup attributional bias theory, received no support from Han and Uygur participants in studies 1 and 2. Several previous studies (e.g., Islam & Hewstone, 1993;Khan & Liu, 2008;Stephan, 1977) have revealed a similar pattern. Three possible reasons for this phenomenon could be supposed.…”
Section: Presence Of In-group Favoring Tendency and Absence Of Out-supporting
confidence: 72%
“…The out-group derogating attribution tendency, which is also part of the intergroup attributional bias theory, received no support from Han and Uygur participants in studies 1 and 2. Several previous studies (e.g., Islam & Hewstone, 1993;Khan & Liu, 2008;Stephan, 1977) have revealed a similar pattern. Three possible reasons for this phenomenon could be supposed.…”
Section: Presence Of In-group Favoring Tendency and Absence Of Out-supporting
confidence: 72%
“…This pattern of attributions is known as the “ultimate attribution error (UAE),” and is said to maintain in-group favoritism and out-group stereotyping and prejudice (Pettigrew, 1979). Although the UAE has received some empirical support (Duncan, 1976; Morris & Peng, 1994; Taylor & Jaggi, 1974), overall evidence for both in-group favoring and out-group derogating attributions has been limited (Hewstone, 1990; Khan & Liu, 2008). …”
Section: Intergroup Attributional Biasmentioning
confidence: 99%
“…At the same time, musical ethnocentrism is likely to be driven by similar individual factors as general ethnocentrism and nationalism. Extant research has revealed antecedent associations between ethnocentrism and social dominance orientation (e.g., Khan & Liu, 2008), right-wing authoritarianism (e.g., Altemeyer, 1994), conservation and traditional values (e.g., Balabanis, Mueller, & Melewar, 2002), just to mention a few. Similar personality and value correlates have been reported for music preferences (e.g., Boer et al, 2011;Chamorro-Premuzic & Furnham, 2007;Delsing, ter Bogt, Engels, & Meeus, 2008;Rentfrow & Gosling, 2003).…”
Section: Discussionmentioning
confidence: 99%